Prevention in Health Insurance: a Welfare Analysis of Participating Policies - Francesca Barigozzi; Renaud Bourlès; Dominique Henriet; Giuseppe Pignataro (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2011)
Preventive care should be subsidized in traditional insurance contracts since policyholders ignore the benefit of their prevention choice on the insurance premium (Ellis and Manning, 2007 JHE). We study participating policies as risk-sharing agreements among policyholders who decide how much to invest in secondary prevention. We explore under which conditions these policies allow partial or even full internalization of prevention benefits in an environment with repeated interactions between policy holders. Welfare generated by the risk-sharing agreement is increasing with the size of the pool, but at the same time the pool size must not be too large for cooperation to sustain the internalization benefits.
Keywords: D82; I11; I13; 330